The Agave victoriae-reginae complex (Agavaceae) - González-Elizondo, M. Socorro; González-Elizondo, Martha; López-Enríquez, Irma L.; Reséndiz-Rojas, Lorenzo; Tena-Flores, Jorge A.; Retana-Rentería, Flor Isela (Instituto de Ecología, A.C., 2011)
The name Agave victoriae-reginae has been applied to a group of plants endemic to northern Mexico which are easily distinguished from other species of Agave by having leaves with corneous, entire margins, white lines on both faces and flowers with short, funnelform tubes. A taxonomic revision reveals that A. victoriae-reginae represents a complex of three species, one of them with two subspecies: 1a) Agave victoriae-reginae subsp. victoriae-reginae (western Nuevo León and eastern extreme of Coahuila; 1b) A. victoriae-reginae subsp. swobodae (southern Coahuila and northeastern Durango); 2) Agave nickelsiae (microendemic to southeastern Coahuila); and 3) Agave pintilla (the most westernly distributed species in the group, restricted to southeastern Durango). Agave pintilla is here described as new, the name of A. nickelsiae is reinstated, and A. victoriae-reginae is circumscribed. A key to the taxa as well as ammended descriptions for A. victoriae-reginae subsp. victoriae-reginae, A. victoriae-reginae subsp. swobodae and A. nickelsiae are provided. No natural hybrids were found among the taxa of the Agave victoriae-reginae complex but three natural hybrids with other species are recorded: Agave nickelsiae x A. asperrima, A. nickelsiae x A. lechuguilla, and A. pintilla x A. salmiana subsp. crassispina.